Engineering Applications of Neural Networks 13th International Conference, EANN 2012, London, UK, September 20-23, 2012. Proceedings - Jayne, Chrisina; Yue, Shigang; Iliadis, Lazaros; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
This book constitutes the refereed proceedings of the 13th International Conference on Engineering Applications of Neural Networks, EANN 2012, held in London, UK, in September 2012. The 49 revised full papers presented were carefully reviewed and selected from numerous submissions. The papers describe the applications of neural networks and other computational intelligence approaches to intelligent transport, environmental engineering, computer security, civil engineering, financial forecasting, virtual learning environments, language interpretation, bioinformatics and general engineering.
Intelligent transport -- Environmental engineering -- Computer security -- Civil engineering -- Financial forecasting -- Virtual learning environments -- Language interpretation -- Bioinformatics and general engineering.
Keywords: Computer science; Computer communication systems; Computers; Data mining; Artificial intelligence; Pattern recognition; Application software; Computer Science; Data Mining and Knowledge Discovery; Pattern Recognition; Computer Appl. in Administrative Data Processing; Computation by Abstract Devices; Artificial Intelligence (incl. Robotics).; Computer Communication Networks; Electronic books